Walkability and accessibility around the Unified Educational Centers of São Paulo - Shashiki, Christiane; Mülfarth, Roberta Consentino Kronka (Revista Nacional de Gerenciamento de Cidades, 2023)
The objective of this article is to draw a brief analysis of the walkability and accessibility of the immediate surroundings of some Unified Educational Centers (CEUs) in São Paulo, through the available information on Geosampa and Google Maps websites, related to enrollments in the municipal network in São Paulo. When evaluating the walkability and accessibility in the immediate surroundings of some CEUs in São Paulo, the contrast between the implantation so generous and inviting for the environments inside the CEU and the maintenance of the existing pattern of exclusion of space for the pedestrian’s circulation in its immediate surroundings becomes clear, leading to an invitation to reflect about how we can try to improve walkability in terms of accessibility and safety.